Public Hospital Type C Pekan Labuhan - Nelson M. Siahaan; Audina Muhvira (Talenta Publisher, 2017)
The rapid economic growth in Medan Labuhandistrict has an impact on improving living standards and population growth. This is also in line with the availability of public facilities and infrastructure because the higher the level of one's life, the higher the quality of facilities. Furthermore it is needed a container to full fill the need for medical services both medical and non medical are realized through the design of